2014
DOI: 10.1007/s12010-014-1442-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Point Mutation Detection in Mycobacterium tuberculosis with Isoniazid Resistance Using Real-Time PCR and TaqMan Probe Assay

Abstract: Rapid methods for diagnosis of Mycobacterium tuberculosis (Mtb) drug resistance and choosing appropriate antibiotic treatment are pivotal. Thirty isoniazid (INH)-resistant and 30 INHsusceptible Mtb isolates were evaluated using minimum inhibitory concentration (MIC) method followed by multiplex real-time PCR (RT-PCR). Amplification refractory mutation system (ARMS) for detection of mutation in 315 codon of katG gene and single-nucleotide polymorphism (SNP) for detection of mutation in −15 (C>T) in the regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The conventional point mutation detection methods include sequencing and PCR based methods ( Manam and Nichols, 1991 ; Riahi et al, 2015 ). The basic mutation site recognition strategies include surface ligation reaction, mismatch binding protein mediated strategy, molecular beacon-based method and fluorescence in situ hybridization (FISH) ( Sun et al, 2018 ; Lu et al, 2020 ).…”
Section: Traditional Point Mutation Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conventional point mutation detection methods include sequencing and PCR based methods ( Manam and Nichols, 1991 ; Riahi et al, 2015 ). The basic mutation site recognition strategies include surface ligation reaction, mismatch binding protein mediated strategy, molecular beacon-based method and fluorescence in situ hybridization (FISH) ( Sun et al, 2018 ; Lu et al, 2020 ).…”
Section: Traditional Point Mutation Detection Methodsmentioning
confidence: 99%
“…PCR based methods, such as PCR based allele detection system (AS-PCR) and fluorescent gene detection technology, allele specific small groove binding probe real-time PCR detection (RT-PCR), PCR restriction fragment length polymorphism (RFLP), polymerase chain reaction single strand conformation polymorphism (PCR-SSCP) and heteroduplex mobility analysis (HMA) belong among the most commonly used point mutation detection methods ( Callens and De Clercq, 1999 ; Pozzi et al, 2009 ; Riahi et al, 2015 ; Prykhozhij et al, 2018 ).…”
Section: Traditional Point Mutation Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, molecular diagnosis of encephalitis was confirmed according to HSV-1 and 2 or tuberculosis real-time PCR on CSF. Primers and labeled probes for tuberculosis qRT-PCR, TaqMan method, were used as previously described (20). The standard TaqMan master mix (Takara, Japan) was used for qRT-PCR amplifications.…”
Section: Qrt-pcr Taqman Methodsmentioning
confidence: 99%
“…There are many methods for SNP genotyping, including MALDI‐TOF mass spectrometry, Taqman probe, restriction fragment length polymorphism (RFLP), microarray, and DNA sequencing . Due to the high cost, MALDI‐TOF mass spectrometry, microarray, and DNA sequencing are not suitable for analysis of large samples.…”
Section: Introductionmentioning
confidence: 99%